Combining genomewide association study and lung eQTL analysis provides evidence for novel genes associated with asthma. Issue 12 (22nd August 2016) - Nieuwenhuis, M. A.; Siedlinski, M.; van den Berge, M.; Granell, R.; Li, X.; Niens, M.; van der Vlies, P.; Altmüller, J.; Nürnberg, P.; Kerkhof, M.; van Schayck, O. C.; Riemersma, R. A.; et al.
Abstract: Background: Genomewide association studies (GWASs) of asthma have identified single‐nucleotide polymorphisms (SNPs) that modestly increase the risk for asthma. This could be due to phenotypic heterogeneity of asthma. Bronchial hyperresponsiveness (BHR) is a phenotypic hallmark of asthma. We aim to identify susceptibility genes for asthma combined with BHR and analyse the presence of cis‐ eQTLs among replicated SNPs. Secondly, we compare the genetic association of SNPs previously associated with (doctor's diagnosed) asthma to our GWAS of asthma with BHR. Methods: A GWAS was performed in 920 asthmatics with BHR and 980 controls. Top SNPs of our GWAS were analysed in four replication cohorts, and lung cis‐eQTL analysis was performed on replicated SNPs. We investigated association of SNPs previously associated with asthma in our data. Results: A total of 368 SNPs were followed up for replication. Six SNPs in genes encoding ABI3BP, NAF1, MICA and the 17q21 locus replicated in one or more cohorts, with one locus (17q21) achieving genomewide significance after meta‐analysis. Five of 6 replicated SNPs regulated 35 gene transcripts in whole lung. Eight of 20 asthma‐associated SNPs from previous GWAS were significantly associated with asthma and BHR. Three SNPs, in IL‐33 and GSDMB, showed larger effect sizes in our data compared to published literature. Conclusions: Combining GWAS with subsequent lung eQTL analysis revealed disease‐associated SNPs regulating lung mRNA expression levels of potential new asthma genes. Adding BHR to the asthma definition does not lead to an overall larger genetic effect size than analysing (doctor's diagnosed) asthma.